2015
DOI: 10.1097/gme.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum 25-hydroxyvitamin D and ovarian reserve in premenopausal women

Abstract: Objective Vitamin D has been linked to anti-Müllerian hormone levels, suggesting a possible association with greater ovarian reserve, but large population-based studies are lacking. Our objective was to explore the association between vitamin D and FSH in premenopausal women. Methods The Uterine Fibroid Study (1996 – 1999) enrolled randomly-selected 30 – 49 year-old members of a Washington D. C. health plan (N=1430). Women provided a blood and urine sample in addition to questionnaire data. The vitamin D met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
0
34
2
Order By: Relevance
“…However, for dichotomous outcomes, there was a tendency for insufficient 25OH-D (<30 ng/mL) to be associated with low AMH (<0.7 ng/mL) (odds ratio (95% CI): 1.8 (0.9-4)). An earlier study by the same group of 527 premenopausal women also suggested an association between the vitamin D level and FSH [60]. They showed an inverse association between 25OH-D and urinary FSH.…”
Section: Observational Studiesmentioning
confidence: 77%
See 1 more Smart Citation
“…However, for dichotomous outcomes, there was a tendency for insufficient 25OH-D (<30 ng/mL) to be associated with low AMH (<0.7 ng/mL) (odds ratio (95% CI): 1.8 (0.9-4)). An earlier study by the same group of 527 premenopausal women also suggested an association between the vitamin D level and FSH [60]. They showed an inverse association between 25OH-D and urinary FSH.…”
Section: Observational Studiesmentioning
confidence: 77%
“…The median 25OH-D level was 12 ng/mL, with approximately 75% of participants below the recommended level of 20 ng/mL. For an increase of 10 ng/mL in 25OH-D, urinary FSH decreased by 14% (95% confidence interval: −23%-−5%), p = 0.003 [60]. A study of Korean women of similar reproductive ages by Kim et al, however, did not find a correlation between serum vitamin D and AMH levels [45].…”
Section: Observational Studiesmentioning
confidence: 94%
“…Laboratory evidence suggests that the ovary is a target organ for 1,25-dihydroxyvitamin D 3 , the active metabolite of vitamin D 3 , and that vitamin D receptors are expressed in reproductive tissues including the ovary (21,22). Recently, one group observed that plasma 25-hydroxyvitamin D [25(OH)D] 9 concentrations were positively associated with ovarian reserve, providing further evidence of a protective role of vitamin D on ovarian aging (23).…”
Section: Introductionmentioning
confidence: 94%
“…Various studies have confirmed that lower serum 25(OH)D levels were associated with irregular menstrual cycles [ 87 ]. Vitamin D may also influence the ovarian reserve and is inversely related to FSH level, as was demonstrated by Jukic et al [ 88 ].…”
Section: Discussionmentioning
confidence: 88%